Optimal recovery of elements from Hilbert space and their scalar products by Fourier coefficients known with error - Gunko, M. S.; Babenko, V. F.; Parfinovych, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5 In a Hilbert space defined as the image of the unit ball under the action of a compact operator, we solve problems of optimal recovery of elements by their first n Fourier coefficients given approximately. Similar problems are also solved for scalar products of elements from two different classes.